Doxycycline compared to prednisolone therapy for patients with bullous pemphigoid: cost-effectiveness analysis of the BLISTER trial - Mason, James M.; Chalmers, J.R.; Godec, Thomas R.; Nunn, Andrew J.; Kirtschig, Gudula; Wojnarowska, Fenella; Childs, Margaret; Whitham, Diane; Schmidt, Enno; Harman, Karen; Walton, Shernaz; Chapman, Anna; et al. (Wiley, 2018)
Background: Bullous pemphigoid (BP) is an autoimmune blistering skin disorder associated with significant morbidity and mortality. Doxycycline and prednisolone to treat bullous pemphigoid were compared within a randomised controlled trial (RCT).